The Development of Enrichment Books of Writing Short Story Text which Contains Local Wisdom as an Alternative Learning Material in Short Story Text Writing Learning (Universitas Negeri Semarang, 2019)
The development of enrichment book is needed to support the learning process. The enrichment book is a textbook companion book. The use of this book is important. The availability of enrichment books is still small. This enrichment book meets the characteristics of the curriculum 2013, based on the text genre. The purpose of this research is to develop an enrichment book of writing short story text which contains local wisdom. The content of local wisdom is integrated to inspire students’ awareness to love and appreciate local wisdom as well as to follow the values of local wisdom. This research used Research and Development (R&D) research design from Borg, and Gall. The result of this research is the enrichment book of writing short story text which contains local wisdom as alternative learning material in short story text writing material. The existence of local wisdom can be used as a means of learning in instilling positive values. Also, the book is capable of creating innovative learning